Políticas públicas para acesso de pessoas com deficiência ao ensino superior brasileiro: Uma análise de indicadores educacionais - Martins, Diléia Aparecida; Leite, Lúcia Pereira [UNESP]; de Lacerda, Cristina Broglia Feitosa (FapUNIFESP (SciELO), 2015)
This study sought to analyze the enrollment policies for special education in Brazilian higher education programs derived from educational indicators. The study is characterized as analytic-descriptive and was based on primary sources; they included technical reports and data from the Brazilian Higher Education Census Bureau from 2000 to 2011, as well as documents from the country's accessibility program known as Include (Incluir, in original Portuguese) from 2005 to 2011. The decade in question was selected in line with understanding the federal government's measures planned in the country's National Education Plan, which were focused on increasing enrollment in Brazilian higher education programs. The need to question the results of the aforementioned measures also justified the choice of the period to be studied. The data analysis revealed an increase in the number of disabled students enrolled in traditional and online undergraduate degree programs (particularly at Brazilian public universities) following the initiation of the Include Program. Overall, enrollments among disabled students in higher education programs increased in terms of numbers; however, the percentage still represents only a small part of the disabled population.
Public policy for disabled persons' access to higher education in Brazil: An analysis of educational indicators
Keywords: Educational indicators; Higher education; Special education